2021
DOI: 10.1007/s00330-021-07992-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of artificial intelligence support on accuracy and reading time in breast tomosynthesis image interpretation: a multi-reader multi-case study

Abstract: Objectives Digital breast tomosynthesis (DBT) increases sensitivity of mammography and is increasingly implemented in breast cancer screening. However, the large volume of images increases the risk of reading errors and reading time. This study aims to investigate whether the accuracy of breast radiologists reading wide-angle DBT increases with the aid of an artificial intelligence (AI) support system. Also, the impact on reading time was assessed and the stand-alone performance of the AI system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Our findings are also agreeing with smaller scale studies [11][12][13][14][15][16]. Rodriguez-Ruiz et al [17] in 2019, performed a study on 240 mammograms (100 cancers, 40 leading to false-positive recalls, 100 normal) reported that sensitivity increased with AI support to 86% vs 83% with mammography alone.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are also agreeing with smaller scale studies [11][12][13][14][15][16]. Rodriguez-Ruiz et al [17] in 2019, performed a study on 240 mammograms (100 cancers, 40 leading to false-positive recalls, 100 normal) reported that sensitivity increased with AI support to 86% vs 83% with mammography alone.…”
Section: Discussionsupporting
confidence: 91%
“…To verify the CAD model's correlation associated with radiologists' experience, we focused only on mass, which is an uncomprehensive system for all the signs in breast lesions. Second, compared with other similar studies, where an average of 16.4 radiologists participated in the reader study (34)(35)(36)(37)(38), the number of readers in MRMC was relatively small in our study. Moreover, this study did not set two replicate experiments to verify the agreements for the same radiologist in different reading times.…”
Section: Discussionmentioning
confidence: 58%
“…While there are several studies of AI for DM, studies of AI for DBT are relatively scarce, with only a few studies of DBT on screening material at the time of writing, including two focusing on DBT reading workload reduction [18][19][20][21]. Several reader studies on the use of AI as decision support for DBT with cancerenriched datasets have shown a reduction in reading time per examination with maintained or increased accuracy [22][23][24][25][26][27]. An AI model for predicting future short-term cancer risk from DBT has also been developed [28].…”
Section: Introductionmentioning
confidence: 99%